Analysis of Climate Change Adaptation Policies in Asia - Michalak, Dorota; Szyja, Paulina (Comparative Economic Research. Central and Eastern Europe, 2024)
The article addresses the issue of adaptation policies by comparing two regions in Asia: Southeast Asia and Northeast Asia. The aim is to highlight the directions and the degree of progress of the policies implemented, as well as their determinants. The methodology included an analysis of bibliographic materials and available data. As a result, it was possible to establish that the scope of carrying out adaptation policies varies depending on the country, and it is not possible to speak of a common continental policy or even a common regional policy. The degree of a country’s development determines the sophistication of the policy pursued.